Comparing conservation and animal welfare professionals' perspectives on domestic cat management. (August 2022) - Crowley, Sarah L.; DeGrange, Lauren; Matheson, David; McDonald, Robbie A.
Abstract: Debates about managing roaming and hunting behaviours in domestic cats often appear to fracture along lines of biodiversity conservation and animal welfare. In practice, however, there may be no inherent opposition between these interests. We carried out a series of Q methodological studies with people in the UK who were professionally engaged either with wildlife conservation or with animal welfare, and who had key individual stakeholder roles as cat owners. Participants arranged a set of statements according to their perspectives on roaming and hunting behaviours and on cat husbandry practices. Analysing the two professional groups together, we found three distinct perspectives: 'Conservationist', concerned about cat impacts on wildlife populations; 'Welfarist', focused on ensuring cat safety and wellbeing, and 'Liberationist', prioritising cat behavioural freedom. Analysing responses within the professional groups, however, we found that cat owners from both conservation and welfare organisations held perspectives that had much in common, and either (a) supported active management of roaming and hunting behaviour, (b) tolerated hunting behaviour as either desirable or unavoidable, or (c) were conflicted, supporting outdoor access for cats but expressing concern about hunting behaviour and cat safety. While their priorities may differ, cat owners working as conservation professionals were cognisant of cat welfare considerations, and animal welfare professionals were often also concerned about wildlife, particularly wild animal welfare. We also identified important areas of agreement on night-time confinement and regulation of cat breeding. This research highlights valuable opportunities for constructive dialogue and greater collaborative working among conservation and animal welfare organisations.